University Belongingness Scale: Measurement and Construct Verification in Indonesian Language - Triantoro Safaria (Institute of Advanced Engineering and Science, 2013)
Sense of belonging is the extent to which person feels attached, related and belong in organization system. If, a person feels accepted, comfortable, congruence and get recognition from an organization, this condition will motivate the person to share positive contribution to their organization. The problem with Ahmad Dahlan University is a low student sense of belonging to their university. This condition will cause negative effects for university in the future, with increasing several students’ negative behaviors such as apathy, unresponsiveness, until higher students drop out. It is needed to evaluate and understand the student’s sense of belongings to their university, in order to take preventive action related to a low sense of belongings of students. The aim of this study is to create and develop a sense of belongingness measurement for Ahmad Dahlan University Belongingness Scale (ADUBS), that it will be used to evaluate how high the student sense of belonging to their university. The result of exploratory factor analysis (EFA) showed two dimensions the sense of belongingness constructs that represent the sense of belongings of student to their university namely University belongings and Community belongings. The next result from confirmatory factor analysis (CFA) using structural equation modeling (SEM) confirms that measurement model of ADUBs was fitted with empirical data (Chi-square = 39.054, with p > .001, degree of freedom = 36, CMIN = 1.085, RMSEA =. 022, NFI = .918, TLI = .989, GFI= .961, and CFI= .993.DOI: http://dx.doi.org/10.11591/ijere.v2i1.1667